The ability of GLIM and MNA-FF to diagnose malnutrition and predict sarcopenia and frailty in hospitalized adults over 60 years of age - da Silva, Gabriella D.; Batista, Afra V. De A.; Costa, Maria C. R. De A.; dos Santos, Ana C. O. (Frontiers in Nutrition, 2024)
Introduction Malnutrition remains common in adults over 60 years old. Although there are screening and diagnostic tools for malnutrition, there is no globally used approach to diagnosing malnutrition in older adults admitted to the hospital. In this study, we verified the agreement between the Global Leadership Initiative on Malnutrition (GLIM) and the Mini Nutritional Assessment (MNA) and the ability of the instruments to identify frailty and sarcopenia associated with malnutrition. Methods For adults over 60 years old, malnutrition diagnosis was performed using the Mini Nutritional Assessment Full Form (MNA-FF) tool and the GLIM criteria, which included calf circumference and fat-free mass index to assess muscle mass, with and without the Mini Nutritional Assessment Short Form (MNA-SF) screening. Health conditions were assessed in older adults, and the association of these conditions with malnutrition was analyzed using both tools. Results A total of 432 adults over 60 years old were investigated with a mean age of 71.14 ± 8 years. The GLIM criteria with the nutritional screening tool identified 61–63% of older adults as malnourished. Of these, 63–64% were severely malnourished. The MNA-FF tool classified 20% of those assessed as malnourished. The agreement between the MNA-FF and GLIM was better with the use of screening, with a kappa (K) value of −0.10 and − 0.11. Sarcopenia was associated with malnutrition as identified by the MNA-FF (OR: 3.08, 95% CI: 1.84–5.14) and only by the GLIM ANTHRO (OR: 1.66, 95% CI: 1.05–2.63). Frailty was associated with the MNA-FF (OR: 15.99, 95% CI: 2.16–118.36), GLIM ANTHRO (OR: 2.21, 95% CI: 1.31–3.71), and GLIM BIA (OR: 2.45, 95% CI: 1.45–4.12). Conclusion It is possible to verify that divergent conceptual frameworks are used to understand malnutrition by the MNA-FF and GLIM and that the GLIM obtained a greater number of malnutrition diagnoses. Both the GLIM ANTHRO and the MNA-FF associated malnutrition with frailty and sarcopenia, with higher hazard ratios for the MNA-FF.